Cushing’s Disease Management: Glimpse Into 2051 - Dalan, Rinkoo; Bornstein, Stefan R.; Boehm, Bernhard O. (Frontiers in Endocrinology, 2022)
Major advancements are expected in medicine and healthcare in the 21st century- “Digital Age”, mainly due to the application of data technologies and artificial intelligence into healthcare. In this perspective article we share a short story depicting the future Cushings’ Disease patient and the postulated diagnostic and management approaches. In the discussion, we explain the advances in recent times which makes this future state plausible. We postulate that endocrinology care will be completely reinvented in the Digital Age.